Strategy Improving Students 'Visit To Library Through Convenience, Facilities And Collections And Interest To Read (Case Study: Public Library and Archives of Lamongan District) - Mu`ah Mu`ah (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2017)
The development of education in Indonesia is inseparable from the role of the library, because the library is an information center or information center. So to increase the visit to the library required facilities and infrastructure in accordance with its development. This study aims to analyze the factors that can affect the increase of student visits to the library. This study aims to explain whether the convenience variables, collections, facilities and interests can increase the number of visits students read. Population in this research is all visitor of student of Public Library and Archive of Lamongan Regency. The entire population and sample were 80 students who used total sampling or whole population were sampled because the population was less than 100. The instrument used in this study was questionnaire. Based on the results of data analysis shows that the indicators used in this study Interest in Student Visits and Quality Library showed significant results with the value of t count of convenience 41,630, collection 7, 003 and 7,849 facilities. This value is greater than 1.96. In addition, a significance level of 0.000 (P <0.05) was obtained. Therefore to increase Interest in student visits significantly influenced by the quality of the library including convenience, facilities, and collections. Students' perceptions of strategies to increase traffic applied by Lamongan Public Library and Archives are getting better (positive), so student visits to the General Archives and Regional Archives of Lamongan District will increase. With the addition of convenience, facilities and collections so as to provide excellent service to students.